HSV-1 amplicon vectors launch the production of heterologous rotavirus-like particles and induce rotavirus-specific immune responses in mice - Laimbacher, Andrea S. (2011)
Virus-like particles (VLPs) are promising vaccine candidates because they represent viral antigens in the authentic conformation of the virion and are therefore readily recognized by the immune system. As VLPs do not contain genetic material they are safer than attenuated virus vaccines. In this study, herpes simplex virus type 1 (HSV-1) amplicon vectors were constructed to coexpress the rotavirus (RV) structural genes VP2, VP6, and VP7 and were used as platforms to launch the production of RV-like particles (RVLPs) in vector-infected mammalian cells. Despite the observed splicing of VP6 RNA, full-length VP6 protein and RVLPs were efficiently produced. Intramuscular injection of mice with the amplicon vectors as a two-dose regimen without adjuvants resulted in RV-specific humoral immune responses and, most importantly, immunized mice were partially protected at the mucosal level from challenge with live wild-type (wt) RV. This work provides proof of principle for the application of HSV-1 amplicon vectors that mediate the efficient production of heterologous VLPs as genetic vaccines.